Przeciw nakazom niepamięci – wariant Elif Shafak - Czyżak, Agnieszka (Slavia Occidentalis, 2015)
The main aim of the article is the return to the historical events which happened on the Turkish territory of the Ottoman Empire in 1915 and to identify traces of the past. During the First World War the attempted extermination of the Armenian nation took place, and those tragic occurrences remain a literary theme until now. An interpretation of the novel written by Elif Şafak – almost a hundred years after those events – leads to some rather pessimistic cultural conclusions. The author creates, in The Bastard of Istanbul, a mournful vision of the common tendency to forget and the mutual agreement to inherit prejudices against members of other nations, but especially those who live in neighbouring areas.